With many voices: the sea in Victorian fiction - Kerr, MPM (2013)
This thesis considers some of the ways in which the sea was written about and written with in English nineteenth-century prose fiction. It has become a commonplace of literary criticism that, in the century preceding modernism, prose fiction about the sea was unthinking and uninteresting: indentured to outworn generic codes, tied to certain clichés of national identity, Empire, or slipshod sublimity, and vaguely evoking some or all of them. This thesis does not attempt a general contradiction of this view. What this thesis does suggest is that Victorian fiction is not always naïve about its subject and, at times, displays an awareness of the generic and stylistic hazards attendant upon writing about the sea. To write about the sea was to risk writing vaguely. However, to Victorian novelists who wished to draw on vagueness, the sea offered a subject and a style that could be put to use. The introduction sets out the terms of my discussion both of vagueness, and of the attitudes of Victorian writers and readers to the sea as a setting and theme for fiction. The terms of philosophical vagueness are compared with the nineteenth century’s most influential aesthetics of obscurity: the sublime. The purchase of these theories is then tested, first in relation to Ruskin’s lifelong interest in representing the sea in painting and prose, and second with reference to novels by George Eliot, Thackeray, and Gaskell. Prior critical approaches are also considered, as is the topic of empire, which I explain is not my primary focus. The body of the thesis is devoted primarily to three author studies: Frederick Marryat, Charles Dickens, and Joseph Conrad. Each author wrote vaguely about the sea, though vagueness is shown to be, in all three cases, a resource that can be drawn upon with degrees of self-consciousness; if, by the beginning of the nineteenth century, vague language was considered appropriate to the sea, the linguistic resources that the sea in turn offered began to seem increasingly applicable to experiences characterised by uncertainty. I suggest that the sea establishes conditions that invite a rereading of the many repetitions in Marryat’s novels. These repetitions can be viewed, I argue, as traces of Marryat’s struggle to find a language appropriate to the ocean. In Dickens’s writing, the sea is often present as a source both of metaphor and of experience. I suggest that the slippery doubleness of the literary sea is a means by which both Dickens’s characters, and the individuals he encounters as a journalist, can be made to coexist with their ideal or literary doubles. In my chapter on Conrad, I argue that the sea forms a crucial element of the kind of literary impressionism Conrad recommends in his preface to The Nigger of the ‘Narcissus’ (1897) and elsewhere. Vagueness arises when the border between linguistic concepts becomes blurred. Two short interludes, on the subject of shores and depths respectively, consider such permeable thresholds. These interludes also provide a means of charting changes that occurred across the period, a counterpoint to the more temporally specific focus of the author studies. I conclude with a brief discussion of Virginia Woolf’s The Waves (1931). Critics have distinguished the high modernist sea from what came before; this coda insists that the sort of vagueness valued by Woolf has an earlier origin.